The Federal Direct Student Loan Program. CRS Report for Congress - Schenet, Margot A.; Library of Congress, Washington, DC. Congressional Research Service ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1995)
This report discusses the establishment and operation of the Federal Direct Student Loan Program (DL), enacted by Congress in 1993 to partially replace the existing federal guaranteed student loan programs with a single program that would make loans directly to postsecondary students through their schools. The DL program will be phased in over a 5-year period so that it will originate at least 60 percent of all new federal loans to students during the 1998-99 academic year. The new DL program includes four different repayment plans: standard, graduated, extended, and income-contingent. The development of the income-contingent plan was particularly controversial, since it was estimated that 52 percent of borrowers would be subject to negative amortization at some time during the loan life, increasing their debt. Other concerns about the DL program include its impact on the general availability of loan aid for students, the ability of the U.S. Department of Education to administer the program, and the program costs. (MDM)
ERIC Note: For a related document, see HE 028 025.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Students; Educational Attitudes; Federal Aid; Federal Programs; Financial Support; Government Role; Loan Repayment; Postsecondary Education; Program Descriptions; Program Evaluation; Program Implementation; Public Policy; Student Financial Aid; Student Loan Programs; Direct Lending; Legal/Legislative/Regulatory Materials